Surgical pediatric otolaryngology - Potsic, William P.; Cotton, Robin T. (Robin Thomas), 1941-; Handler, Steven D. (Steven Douglas), 1946-; Zur, Karen B. (Thieme, 2016)
This revised edition of Surgical Pediatric Otolaryngology provides readers with step-by-step instructions for performing the surgical procedures necessary to treat children suffering from head and neck disorders. This atlas covers routinely performed procedures in pediatric otolaryngology. Key Features: More than 800 high-quality, detailed line drawings help teach young practitioners the latest techniques and procedures; Authors are affiliated with two of the best children's hospitals in the world and are luminaries in the field; Focuses on common procedures that surgeons perform on a daily basis